Consciousness and Perceptual Experience : an Ecological and Phenomenological Approach. - Natsoulas, Thomas (Cambridge University Press, 2013)
An unusual study of human perceiving from the perspective of an ecological psychology that explicitly incorporates a phenomenology of consciousness.